2014
DOI: 10.1093/cvr/cvu222
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 suppresses cardiac neovascularization by down-regulating VEGF and PlGF expression

Abstract: E2F1 limits cardiac neovascularization and functional recovery after MI by suppressing VEGF and PlGF up-regulation through p53-dependent and -independent mechanisms, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 44 publications
3
38
1
Order By: Relevance
“…In cardiac fibroblasts subjected to hypoxia, the overexpression of E2F1 increased the expression of TP53, which was required to repress the expression VEGF-A; while a decrease in PIGF occurred independently of the TP53 status of these cells. These results suggested that E2F1 promotes the expression of pro-angiogenic factors through both TP53-dependent and TP53 independent mechanisms (Wu et al, 2014). Conversely to previous observations made in tumor cells, MDM2-deficiency in cardiac cells was reported to enhance E2F1 transcriptional activity and to have detrimental effects on the heart homeostasis (Hauck et al, 2017) (see below Part 'Insight from MDM2 transgenic mice').…”
Section: Mdm2 E2f1 and The Ischemic Heartmentioning
confidence: 82%
See 2 more Smart Citations
“…In cardiac fibroblasts subjected to hypoxia, the overexpression of E2F1 increased the expression of TP53, which was required to repress the expression VEGF-A; while a decrease in PIGF occurred independently of the TP53 status of these cells. These results suggested that E2F1 promotes the expression of pro-angiogenic factors through both TP53-dependent and TP53 independent mechanisms (Wu et al, 2014). Conversely to previous observations made in tumor cells, MDM2-deficiency in cardiac cells was reported to enhance E2F1 transcriptional activity and to have detrimental effects on the heart homeostasis (Hauck et al, 2017) (see below Part 'Insight from MDM2 transgenic mice').…”
Section: Mdm2 E2f1 and The Ischemic Heartmentioning
confidence: 82%
“…Interestingly, E2F1-deficient mice show improved cardiac function, reduced size of myocardial infarction, and enhanced post-infarction cardiac angiogenesis after ligation of the left anterior descending coronary artery. These beneficial effects of E2F1 deficiency in the ischemic heart were due to an upregulation of pro-angiogenic factors (i.e., vascular endothelial growth factor A, VEGF-A and placental growth factor, PIGF (Wu et al, 2014). In cardiac fibroblasts subjected to hypoxia, the overexpression of E2F1 increased the expression of TP53, which was required to repress the expression VEGF-A; while a decrease in PIGF occurred independently of the TP53 status of these cells.…”
Section: Mdm2 E2f1 and The Ischemic Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…53 In the SU5416 group, animals were treated with a SU5416 intraperitoneal injection (Selleck Chemical, 25 mg/kg, every 3 days) from 1 day after Lenti-HRE-MMP-9 brain injection. 54 The vehicle SB-3CT and SU5416 were dissolved in 10% DMSO normal saline solution. The control groups also received the same amount of 10% DMSO NS solution injections.…”
Section: Experimental Designmentioning
confidence: 99%
“…In fact, a pronounced reduction of VEGF production by SLMP53-1 was observed in p53-expressing cancer cells. Indeed, it was reported that p53 indirectly suppresses VEGF expression by repressing transcription factors like SP1 [39] and E2F [40,41]. Interestingly, SLMP53-1 also inhibited the VEGF expression levels in endothelial cells, an effect associated with reduction in cell tube formation.…”
Section: Discussionmentioning
confidence: 98%